Climate, vegetation, vertebrates and soil/litter invertebrates of mediterranean-type ecosystems - data banks - Majer, Jonathan; Catling, P.C.; Daget, P.H.; Greenslade, P. (1988)
The objectives of the Data-Source Book are to collate relevant parameters which appear to control the structure and function of major ecosystems (and component plant and animal species) in the mediterranean-climate regions ofthe world (southern Australia, California-Arizona, Chile, the Mediterranean Basin, Cape Province of South Africa).